Levantamento da extração de areia no município de Juruti-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The present study carried out a survey of sand extraction in the municipality of Juruti-PA based on mining and the environment, as well as its effects on the lives of people, communities and spaces that were degraded during the extraction process. Some specific actions were carried out, such as: identification of the types of impacts caused to the environment; verification of legislation for environmental licensing and exploration of sand mining in the municipality; presentation of undertakings with sand extraction activities; exposition of the legal and illegal practices of the exploitation of this mineral good in the referred municipality. A case study of the problems in the field of investigation was carried out, both of the primary data (observation of the sand extraction areas and the companies visited) and of the secondary data (the current legislation and the documents provided by Organs competent bodies). The methodology adopted was bibliographical research, which was used according to the vision of specialists in the area and their publications, as well as, in the verification of legislation and official documents of the competent bodies. In addition, materials collected in the field research were used, which allowed for deeper diagnoses and analysis of the data collected on the companies, the extraction areas, as well as their operating license. From the results obtained and the analyzes carried out, it was verified that in the municipality of Juruti there are three regularized licensing processes and only two companies that legally work in sand extraction. It was noted that even with regularized processes, it could be observed through photographic records, that there is a place that was exploited illegally, in which it was observed the alteration of the natural landscape of the place and the silting of a stream, which caused impacts to the environment of the explored area. In this way, even if there are companies that work in accordance with the laws that govern the exploration and extraction of mineral goods, there will always be companies or people that circumvent the legislation, in order to obtain profits, without the slightest concern for the environment.
Keywords: Extração de areia; Legislação; Impactos ambientais; CNPQ:: CIÊNCIAS EXATAS